Hyperthermia treatment planning for cervical cancer patients based on electrical conductivity tissue properties acquired in vivo with EPT at 3 T MRI. (3rd July 2016) - Balidemaj, Edmond; Kok, Henny Petra; Schooneveldt, Gerben; van Lier, Astrid L.H.M.W.; Remis, Rob F.; Stalpers, Lukas J.A.; Westerveld, Henrike; Nederveen, Aart J.; van den Berg, Cornelis A.T.; Crezee, Johannes
Abstract: Introduction The reliability of hyperthermia treatment planning (HTP) is strongly dependent on the accuracy of the electric properties of each tissue. The values currently used are mostly based on ex vivo measurements. In this study, in vivo conductivity of human muscle, bladder content and cervical tumours, acquired with magnetic resonance-based electric properties tomography (MR-EPT), are exploited to investigate the effect on HTP for cervical cancer patients.Methods Temperature-based optimisation of five different patients was performed using literature-based conductivity values yielding certain antenna settings, which are then used to compute the temperature distribution of the patient models with EPT-based conductivity values. Furthermore, the effects of altered bladder and muscle conductivity were studied separately. Finally, the temperature-based optimisation was performed with patient models based on EPT conductivity values.Results The tumour temperatures for all EPT-based dielectric patient models were lower compared to the optimal tumour temperatures based on literature values. The largest deviation was observed for patient 1 with ΔT90 = −1.37 °C. A negative impact was also observed when the treatment was optimised based on the EPT values. For four patients ΔT90 was less than 0.6 °C; for one patient it was 1.5 °C.Conclusions Electric conductivity values acquired by EPT are higher than commonly used from literature. This difference has a substantial impact on cervical tumour temperatures achieved during hyperthermia. A higher conductivity in the bladder and in the muscle tissue surrounding the tumour leads to higher power dissipation in the bladder and muscle, and therefore to lower tumour temperatures.